Pregnane Glycosides from Cynanchum marnierianum Stimulate GLP-1 Secretion in STC-1 Cells - Tsoukalas, Michail; Muller, Christian D.; Lobstein, Annelise; Urbain, Aurélie (Planta Medica, 2016)
In the framework of the search for natural glucagon-like peptide-1 secretagogues, the bioassay-guided fractionation of the ethanolic extract from Cynanchum marnierianum led to the isolation of two new pregnane glycosides named marnieranosides A (1) and B (2). The structures were determined based on spectroscopic data and were established as 12β,20 S-O-dibenzoyl-pregn-6-en-5α,8β,14β,17β-tetraol-3-O-β-D-oleandropyranosyl-(1 → 4)-β-D-cymaropyranoside (1) and 12β,20R-O-dibenzoyl-pregn-6-en-5α,8β,14β-triol-3-O-β-D-oleandropyranosyl-(1 → 4)-β-D-canaropyranosyl-(1 → 4)-β-D-cymaropyranoside (2). They present structural analogies to pregnanes previously described in species known for their appetite suppressant and antihyperglycemic effects, such as P57 from Hoodia gordonii. Lupeol (3), a known dipeptidyl peptidase-4 inhibitor, and the insulinomimetic kaempferol-3-O-neohesperidoside (4) were also identified in C. marnierianum. In an in vitro assay on secretin tumor cell line-1 cells, compounds 1, 2, and P57 were found to stimulate the secretion of GLP-1 by 130 % (all tested at 100 µM). These results suggest that C. marnierianum could be of great interest in the treatment of type 2 diabetes, and that pregnane derivatives should be partly responsible via the stimulation of glucagon-like peptide-1 secretion.
Keywords: Cynanchum marnierianum; Apocynaceae; marnieranosides; pregnanes; GLP-1; cytotoxicity